Surgical repair of cervical internal carotid artery aneurysm in a patient with suspected connective tissue disorder - Carlo Campesi; Daniele Mascia; Germano Melissano (Angiologia e Cirurgia Vascular)
BACKGROUND: We present an uncommon case of open surgical treatment of an impacting extra-cranial internal carotid artery aneurysm in a 65-year-old female patient which represented the tip of a large iceberg, in this case, presence of a connective tissue disorder (CTD).